(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
Prickle sensation is a key factor influencing the comfort of dressing. In this paper, the diameter, quantity and fiber bending property of hairiness on the surface of linen fabrics are measured after modification treatment of linen fiber. Meanwhile, the prickle sensation of linen clothing is evaluated by dressing experiments. And the changes of surface hairiness, fiber bending performance and their influences on the dressing prickle sensation of linen clothing are analyzed before or after the modification treatment of linen fiber. The results show that the diameter of the surface hairiness becomes thinner and much more in quantity after modification treatment, but the bending rigidity decreases. Furthermore, the perception value of prickle sensation of linen clothing after modification treatment decreases whether it is under sweating condition or not.